Analysis of Cooperatives’ Perceptions in Kediri City Regarding the Implementation of Circular Letter (SE) No. 7 of 2023 from the Deputy for Cooperatives on Self-Declaration - Munif Achmad; Yani Ahmad; Mauludin M. Soleh (Journal of Public Power, 2026)
The self-declaration policy is a crucial mechanism under the P2SK Act and Circular Letter of the Deputy for Cooperatives No. 7 of 2023 for classifying cooperative business models as either closed-loop (member services) or open-loop (public financial services). This study aims to analyse the perceptions and literacy of cooperative managers in Kediri City regarding the implementation of this policy to ensure the accuracy of business classification and mitigate the risk of administrative sanctions. This study employs a qualitative approach using a phenomenological research design. Data were collected through in-depth interviews with cooperative managers and officials from the Kediri City Cooperative Office, as well as a documentary study of self-declaration files. Data analysis was conducted using an interactive model comprising data reduction, data presentation, and an interpretative approach. The research findings indicate that 100% of the cooperatives in the sample in Kediri City opted for closed-loop status. This decision was driven by a collective desire to preserve the cooperatives’ sociological identity, which is rooted in mutual aid, as well as concerns regarding compliance costs and the strict standards set by the Financial Services Authority (OJK). This decision also serves as a reputational risk mitigation strategy to avoid cognitive dissonance among members, as well as an effort to achieve fiscal efficiency by minimising the potential for higher tax burdens under the open-loop model. Administratively, this policy has triggered a ‘clean-up’ of member data to avoid accusations of shadow banking. This study concludes that whilst the self-declare policy has successfully promoted administrative compliance, there remains a significant communication gap between regulators and industry practitioners regarding the incentives of the open-loop business model.